Emerging pervasive and ubiquitous aspects of information systems cross-disciplinary advancements - Symonds, Judith 1972- (Premier reference source, 2011)
"This book provides an overview of emerging trends in context-aware computing, pervasive and smart environments, as well as research on applications of pervasive technologies in healthcare organizations, work environments, and educational settings" - Provided by publisher